Implementasi Identitas Kependudukan Digital (IKD) Dalam Meningkatkan Pelayanan Publik Di Kota Solok - Sulthan Dzakwan Dhaifullah Windel; Asrinaldi; Aidinil Zetra (Jurnal Niara, 2026)
This study aims to analyze the factors that cause obstacles in the implementation of Digital population identity (IKD) in Solok City and identify the efforts of local governments in overcoming them. This research is motivated by the gap between the achievement of the electronic-based governance system Index (SPBE) of Solok city which is classified as very good with the adoption rate of IKD which is still low and has not reached the national target. The research uses a qualitative approach with Case Study Method. Data was obtained through in-depth interviews with informants from the Department of Population and Civil Registration, Department of communication and Information Technology, Regional Secretariat, Department of investment and One-Stop Integrated Services, Social Services, and the community. Data analysis was conducted using the theory of policy implementation George C. Edwards III covers aspects of communication, resources, disposition, and bureaucratic structure. The results showed that IKD implementation barriers occur in all these variables and are rooted in policy fragmentation between the management of SPBE by the Department of communication and Information Technology and the management of IKD by Disdukcapil. This condition causes the success of SPBE does not have a direct impact on increasing the adoption of IKD. The Solok city government has made various efforts through the expansion of activation, strengthening regulation, institutional cooperation, and public communication innovation, but its effectiveness is still limited due to cross-sectoral regulatory constraints and systemic institutional fragmentation.